Enter a problem...
Algebra Examples
m2-2m+1m-1m2−2m+1m−1
Step 1
Step 1.1
Rewrite 11 as 1212.
m2-2m+12m-1m2−2m+12m−1
Step 1.2
Check that the middle term is two times the product of the numbers being squared in the first term and third term.
2m=2⋅m⋅12m=2⋅m⋅1
Step 1.3
Rewrite the polynomial.
m2-2⋅m⋅1+12m-1m2−2⋅m⋅1+12m−1
Step 1.4
Factor using the perfect square trinomial rule a2-2ab+b2=(a-b)2a2−2ab+b2=(a−b)2, where a=ma=m and b=1b=1.
(m-1)2m-1(m−1)2m−1
(m-1)2m-1(m−1)2m−1
Step 2
Step 2.1
Factor m-1 out of (m-1)2.
(m-1)(m-1)m-1
Step 2.2
Cancel the common factors.
Step 2.2.1
Multiply by 1.
(m-1)(m-1)(m-1)⋅1
Step 2.2.2
Cancel the common factor.
(m-1)(m-1)(m-1)⋅1
Step 2.2.3
Rewrite the expression.
m-11
Step 2.2.4
Divide m-1 by 1.
m-1
m-1
m-1